The Framework of Multicultural Education Value in Indonesia Schools to Face Challenge of 21-Century Learning Using Literary Study - Arini Noor Izzati; Liliana Muliastuti; Zainal Rafli (STAI Hubbulwathan Duri, 2023)
This study uses literary analysis to provide a model for how multicultural education might help Indonesian schools meet the challenges of the twenty-first century. This study fills a knowledge vacuum by employing works of fiction to investigate the importance of intercultural education. The novel Negeri 5 Menara also depicts a multicultural lifestyle and educational system. In this investigation, we employ a qualitative strategy based on content analysis. The study's data comes from a search for examples of intercultural education's core values in literature. This study used a selected data gathering method that Huberman and Miles refer to as